Polymorphism of Congjiang Pigs FUT1 Gene and Its Association with Carcass and Meat Quality Traits. (June 2020) - Zhang, Xiong; Shi, Kaizhi; Wang, Jing; Zhang, Jing; Zhao, Chunping; Du, Chunlin
Abstract: In order to investigate the effects of the M229 and M307 locus in FUT1 gene on the carcass and meat quality of Congjiang pigs. In this study, PCR-SSCP, PCR-RFLP and direct sequencing methods were used to quickly type the M229 and M307 loci, and then the association between different genotypes and meat traits was analysed. Population genetic structure analysis showed that M229 locus of FUT1 gene was in Hardy-Weinberg equilibrium, with high polymorphism information content, rich genetic diversity and large space for directional breeding. However, the M307 locus had the opposite result, showing a skewed distribution. Correlation analysis showed that the average backfat thickness index of CT and TT genotypes from the M229 locus of FUT1 gene in Congjiang pigs was significantly lower than that of CC (P <0.05). The conclusion of this experiment indicates that the M229 locus of FUT1 gene can be strengthened in Congjiang pigs, which can be used for breeding applications.